Semi-automatic collecting load trolley / Muhammad Luqman Mohd Suhardi and Nurulnatisya Ahmad - Mohd Suhardi, Muhammad Luqman; Ahmad, Nurulnatisya (School of Mechanical Engineering, 2023)
A semi-automatic collecting load trolley machine is a mechanism used to ease the lifting of heavy loads and carry the load easily. It can be done by reducing the force needed by using a trolley to carry the load and it can also increase the capacity of the load to be carried. The design of this machine is to improve the working condition mostly for personal use. Thus, the semi-automatic collecting load trolley can be used to move and carry the load in a short distance without using any vehicle such as a forklift which can reduce the cost of transportation. The multimethod of lifting the load such as trolley, fork and other manual lifting had been combined in one mechanism. As a result, this machine will be functioning in good condition and able to help in our daily lives